Probing the acoustic phonon dispersion and sound velocity of graphene by Raman spectroscopy. (August 2019) - Cong, Xin; Li, Qiao-Qiao; Zhang, Xin; Lin, Miao-Ling; Wu, Jiang-Bin; Liu, Xue-Lu; Venezuela, P.; Tan, Ping-Heng
Abstract: The extraordinary thermal and elastic properties of graphene, mainly originating from its unique acoustic phonon branches near Γ point in Brillouin zone, have attracted great attention in its fundamental researches and practical applications. Here, we introduce an optical technique to accurately probe longitudinal acoustic (LA) and transverse acoustic (TA) phonon branches of graphene near Γ point by double resonant Raman scattering of the combination phonon modes in the range of 1650 − 2150 cm −1 along with the overtone 2D ' mode at ∼ 3200 cm −1 . The corresponding sound velocities ( ν T A = 12.9 k m / s, ν L A = 19.9 k m / s ) of graphene have been accessed, which are about 10% smaller than those of graphite. Based on ν T A and ν L A, the two-dimensional (2d) elastic stiffness (tension) coeﬃcients c 11 and c 66, Young ' s modulus Y 2 d and Poisson ' s ratio σ2d can be estimated. The results demonstrate again that double resonant Raman spectroscopy is a powerful tool to probe the fundamental properties of graphene. Graphical abstract: Image 1